ABOUT THE IMPORTANCE OF THE PRINCIPLE OF AUTONOMY OF WILL AND ITS LIMITS IN THE LEGAL SYSTEM - Cárdenas Krenz, Ronald (2015)
This study deals with the principle of autonomy, from some general thoughts about linking technology with several key issues of law and ethics, emphasizing the need for proper training of judges, particularly in terms bioethics, for a proper understanding of human nature. Next, the scope and limits of freedom, especially in the field of law of the People, distinguishing freedom from mere decision, much discussed issue in the field of bioethics are analyzed. Finally, are considering the limits of the autonomy of the volundad are: respect for life, dignity, the principle of autotelia, the best interests of the child, freedom itself, responsibility, public order and good customs reason, fundamental rights, the principles of bioethics, the conditions of validity of the act, the law, morality, personal will own the symmetry principle, the principle of inviolability of the person, etc.